2307. Use of Whole-Genome Sequencing to Determine Adhesin and Biofilm-Associated Gene Profiles Among Pediatric Staphylococcus aureus Device-Related Infection Isolates Compared With Skin and Soft-Tissue Infection Isolates. (26th November 2018) - Foster, Catherine; Kok, Melissa; Flores, Anthony; Luna, Ruth Ann; Kaplan, Sheldon L; Hulten, Kristina G
Abstract: Background: Adhesins or microbial surface component recognizing adhesive matrix molecules (MSCRAMMs) and the ica locus help mediate S. aureus adherence to host tissue and biofilm formation and are thought to play important roles in the pathogenesis of device related infections (DRIs). We hypothesized that S. aureus isolates from pediatric DRIs differ in MSCRAMM and biofilm-associated gene profiles and display greater strain diversity compared with skin and soft-tissue infection (SSTI) isolates. Methods: Patients and isolates were identified from a prospective S. aureus surveillance study at Texas Children's Hospital, 2008–2016. Clinical data were collected retrospectively. Age and date of infection matched SSTI control isolates were selected 4:1. Isolates were genotyped by pulsed-field gel electrophoresis. Whole genome sequencing was performed (Illumina MiSeq). Data were analyzed with CLC Genomics Workbench for the presence of MSCRAMMS ( clf A, clf B, ebh, fbp, fnbp A, fnbp B, isd A, isd B, sdr C, sdr D, sdr E), biofilm-associated genes ( icaA, D, B, C ), accessory gene regulator group, and by multilocus-sequence typing (MLST) with eBurst analysis (www.phyloviz.net ). Conditional logistic regression and Fisher's exact were used for analysis (STATA11). Results: Forty-five patients with 47 DRIs were identified (Table 1). Isolates from 47 DRIs and 188 SSTIs were analyzed for the presence of MSCRAMM and biofilm-associated genes. clf A, clf B, fbp, isd A, isd B, and icaA, D, B, C were present among DRIs and SSTIs more than 98% of the time. Isolates from DRIs or SSTIs did not differ significantly in carriage of MSCRAMMs or the ica locus. DRIs were MSSA (34, 72%), nonUSA300 (39, 83%), and belonged to 19 sequence types (STs). SSTIs were MSSA (79, 42%), nonUSA300 (57, 30%), and belonged to 39 STs (Table 2). Among DRI isolates, STs 5 and 8 were most common (23% each, Figure 1). SSTI isolates were predominately ST8 (68%). Conclusion: S. aureus isolates from DRIs were significantly more likely to be MSSA and nonUSA300 ( P < 0.0001 for both) compared with SSTIs. The majority of S. aureus isolates harbored all MSCRAMM and biofilm-associated genes analyzed. Evaluating genetic polymorphisms and gene expression profiles may clarify the role of adhesion genes in the pathogenesis of DRIs vs. SSTIs. Disclosures: All authors: No reported disclosures.